The digital cast of being : metaphysics, mathematics, cartesianism, cybernetics, capitalism, communication - Eldred, Michael (Ontos Verlag ; [Distributed in] North and South America by Transaction Books, 2009)
We live today surrounded by countless digital gadgets and navigate through cyberspace as if it were the most natural thing in the world. This digital cast of being, however, comes from a long history of philosophical and mathematical thinking in which the Western will to productive power over movement has attained its consummation. This study traces the digital dissolution of beings from the Pythagoreans, Plato and Aristotle's ontology via Cartesian mathematical science through to our digitized economy and telecommunications. With an appendix reinterpreting quantum mechanical indeterminacy phe.